2022
DOI: 10.1111/php.13676
|View full text |Cite
|
Sign up to set email alerts
|

Solar Ultraviolet Radiation, Skin Cancer and Photoprotective Strategies in South Africa

Abstract: The most recent data relating to the incidence of, and mortality from, the three commonest forms of skin cancer, namely basal cell carcinoma (BCC), squamous cell carcinoma (SCC) and cutaneous melanoma (CM), in the Black African, Colored, Asian/Indian and White population groups in South Africa are reviewed. While exposure to solar ultraviolet radiation is the major environmental risk factor for BCC in all four groups, for SSC in the White and Asian/Indian groups and for CM in the White group, this is unlikely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…43 This limitation is particularly significant in the context of BCC, SCC and melanoma, where tumours often manifest in sun-exposed areas, like the scalp, forehead, cheeks and forearm. 44,45 Fortunately, it's worth highlighting that an expanding number of gene network databases now offer the capability to segregate mRNA data based on specific body regions. For instance, Gene Expression Omnibus enables investigators to analyse gene expression data from both sun-exposed and sun-protected areas.…”
Section: Ma Jor Open Que S Ti On Smentioning
confidence: 99%
See 1 more Smart Citation
“…43 This limitation is particularly significant in the context of BCC, SCC and melanoma, where tumours often manifest in sun-exposed areas, like the scalp, forehead, cheeks and forearm. 44,45 Fortunately, it's worth highlighting that an expanding number of gene network databases now offer the capability to segregate mRNA data based on specific body regions. For instance, Gene Expression Omnibus enables investigators to analyse gene expression data from both sun-exposed and sun-protected areas.…”
Section: Ma Jor Open Que S Ti On Smentioning
confidence: 99%
“…Additionally, twin studies have consistently revealed a heritability of approximately 55% for melanoma, underscoring the nuanced nature of its pathogenesis beyond mere spontaneous gene polymorphisms 43 . This limitation is particularly significant in the context of BCC, SCC and melanoma, where tumours often manifest in sun‐exposed areas, like the scalp, forehead, cheeks and forearm 44,45 …”
Section: Major Open Questionsmentioning
confidence: 99%
“…The MED of skin type VI is about 8 times higher than that of FST I. The incidence of all types of skin cancer is much greater in skin types I/II than V/VI [29, 30]. Recent studies have shown that protection against SSR‐induced epidermal CPD is dependent on melanin concentration which varies with epidermal location [31].…”
Section: The Role Of Fitzpatrick Skin Type (Fst)mentioning
confidence: 99%
“…2 In fact, UVR is the leading cause of all types of human skin cancer. 3 Skin cancer cases are on the rise in Saudi Arabia due to excessive UVR exposure given the climate nature of the area, which is mostly sunny year-round. 4 Of the main types of skin cancer, 5 basal cell carcinoma (BCC) and squamous cell carcinoma (SCC), are the most common in Saudi Arabia (51.4% and 22.5%, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Although UVR exposure has many beneficial functions, chronic exposure can be harmful 2 . In fact, UVR is the leading cause of all types of human skin cancer 3 . Skin cancer cases are on the rise in Saudi Arabia due to excessive UVR exposure given the climate nature of the area, which is mostly sunny year‐round 4 .…”
Section: Introductionmentioning
confidence: 99%